Measuring health-related quality of life among university students: a scoping review protocol - Marcelo Couto Jorge Rodrigues; Augusto Cezar Rodrigues Rocha; Crislaine Rangel Couto; Filipe Manuel Clemente; Matias Noll; Auro Barreiros Freire; Claudio Andre Barbosa de Lira; Katja Weiss; Thomas Rosemann; Beat Knechtle; Gustavo De Conti Teixeira Costa (Systematic Reviews)
Abstract Background Understanding university students’ health-related quality of life (HRQoL) can help propose strategies that support targeted care for this population and identify issues affecting these individuals. Therefore, it is necessary to identify the commonly used instruments and possible study designs for the university population, enabling the standardization of interventions and instruments to evaluate the HRQoL of university students. We aim to conduct a scoping review to identify the main measurement instruments and key characteristics in studies using HRQoL measures among university students. It is also aimed at identifying the foundations for guiding future research priorities. Methods This review will consider original peer-reviewed articles that used any generic HRQoL measurement instruments exclusively used with university students aged 18–59. Validation, qualitative, language translation, or adaptation studies will be excluded. This review will follow the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The research will be conducted in five electronic databases (PubMed, Embase, Web of Science, Scopus, and SPORTDiscus). Two reviewers will independently screen records using predefined eligibility criteria and extract data using tables. The extracted data will include specific details about the title, authors, year of publication, HRQoL instrument utilized, participants, intervention design, and critical findings. The results will be presented in a narrative summary with data displayed in tabular and diagrammatic formats. Discussion This proposed scoping review aims to provide a comprehensive overview of the existing methods for assessing health-related quality of life in university students. The results will help identify gaps in the literature and establish a foundation for guiding future research priorities. Scoping review registration Registration with Open Science Framework can be found under registration number https://doi.org/10.17605/OSF.IO/FY9GU .